(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article analyzes the general and specific aspects of the mahalla, aspects of the right of citizens of the Republic of Uzbekistan to self-government, the role of the mahallas in the development of people’s spirituality